Scientific and Methodological Foundations of Using Bloom's Taxonomy Criteria in Elementary School Reading Literacy Classes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article, based on an analytical approach, studies the improvement of the scientific and methodological foundations of the use of Bloom's Taxonomy criteria in primary school reading literacy lessons and the role of the analytical approach and BLUM's taxonomy in developing reading literacy in primary school students. The article is aimed at improving the methodological foundations of the use of taxonomy criteria in the formation of reading literacy skills. The approach ensures the development of students' skills of analysis, evaluation, synthesis and independent thinking. The work presents the practical application of the analytical approach and taxonomy criteria, the scientific significance of the effective organization of the reading process in primary education. The level of students' mastery and the possibilities for developing an individual approach are also analyzed.